Do genes determine champions? - Skinner, J. S. (2001)
The genotype is the total combination of all the inherited genes within the body. It represents an individual's genetic potential and plays a major role in determining many of that individual`s anatomical, biochemical, physiological, and behavioral characteristics or phenotypes (e.g., brown eyes, a body mass of 75 kg, or a maximal oxygen intake of 50 mL • kg-1 • min-1). Except for identical twins, people vary in how their genotypes are expressed in various characteristics, (e.g., strength, body weight, blood pressure), and how those characteristics respond to training, to a low-calorie diet, to medication, or to other environmental factors. The major sources of variation in training seem to be the state of certain complex characteristics (phenotypes) before training and the ability of these phenotypes characteristics to adapt to training. Elite athletes are probably those who begin with high levels of the characteristics needed for success in their sport and who exhibit superior adaptations in those characteristics after training. By knowing the genotype, it is not possible to accurately predict how an individual will respond to training or to any other stimulus or whether that individual will become a champion athlete. It is unlikely that genetic engineering or any other technology can be used to reliably produce champion athletes.